Behaviour of composite plate girders with partial interaction - Yatim, Md Y.; Shanmugam, Nandivaram E.; Badaruzzaman, Wan (Journal of Civil Engineering and Management, 2014)
This paper is concerned with the behaviour and strength of composite plate girders in which, the interaction between the steel plate girder and concrete slab is partial. Based on curvature compatibility principle, an approximate method is proposed from which, the shear capacity and deflection at any given load may be determined. The tension field action developed in web panels at the post-buckling stage is incorporated in the solutions. From the results obtained by using the proposed method, it is found that the flexural stiffness and failure load drop with decrease in degree of interaction. Comparisons are made between the results obtained through the proposed method and the corresponding ones from finite element analysis. A satisfactory correlation between the results in terms of behaviour and strength establishes the accuracy of the proposed method. First published online: 24 Oct 2013